Uwarunkowania restrukturyzacji finansowej w amerykańskich przedsiębiorstwach - rys historyczny - Porada-Rochoń, Małgorzata (The Conditions of Financial Restructuring in American Enterprises - a Historical Perspective, 2008)
The paper presents the influence of different factors and phenomena on the necessity of company's financial restructuring in the USA. The author analyzes the historical aspect of conditions of the restructuring process in American companies at the turn of the 1970s, 1980s, 1990s.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 458-465